AvaliaÇÃo do potencial alelopÁtico de extrato de folhas de kielmeyera coriÁcea sobre lactuca sativa L - dos Santos, Valter henrique marinho [UNESP]; Daneluzzi, Gabriel Silva; Silva, Luciana Pereira; Da Silva, Regildo Márcio Gonçalves [UNESP] (My University, 2015)
Kielmeyera coriacea Mart. (Clusiaceae), popularly known as “pau-santo”, is a typical Brazilian cerrado tree known due to its varied secondary metabolites. This study aimed to determine the allelopathic potential of the hydroalcoholic extract of leaves of K. coriacea through bioassays of seed germination, seedling growth and mitotic index of Lactuca sativa L. (lettuce). In addition it was done the tetrazolium assay and a phytochemical screening. The extract concentrations caused alterations in germination parameters, in root growth and in the mitotic index. The phytochemical screening showed the presence of triterpenes, coumarins, steroids, flavonoids and condensed tannins, compounds known to confer allelopathic characteristics upon other species. These data indicate that K. coriacea presents an allelopathic potential because its leaf extracts interfere with germination and growth without any interference of pH and osmotic potential in the results.
Evaluation of allelopathic potential of leaf extract of kielmeyera coriacea on lactuca sativa L
Keywords: Germination Parameters; Kielmeyera coriacea; Mitotic Index; Phytochemical Screening; Seedling Growth